Two HPA axis genes, CRHBP and FKBP5, interact with childhood trauma to increase the risk for suicidal behavior - Roy, Alec; Hodgkinson, Colin A.; DeLuca, Vincenzo; Goldman, David; Enoch, Mary-Anne (Journal of psychiatric research, 2012)
Childhood trauma is associated with hypothalamic–pituitary–adrenal (HPA) axis dysregulation. Both factors increase risk for suicidal behavior. Corticotropin releasing hormone (CRH) regulates the HPA axis and its actions are moderated by a high-affinity binding protein (CRHBP). We hypothesized that CRHBP variation and interaction with childhood trauma might influence suicidal behavior. Moreover, there might be an additive effect with FKPB5, another HPA axis gene previously associated with suicidality in this dataset. African Americans were recruited: 398 treatment seeking patients with substance dependence (90% men; 120 suicide attempters) and 432 non-substance dependent individuals (40% men; 21 suicide attempters). A total of 474 participants (112 suicide attempters) completed the Childhood Trauma Questionnaire (CTQ). Haplotype-tagging SNPs were genotyped across CRHBP and, for completeness, across CRH, CRHR1 and CRHR2. FKBP5 genotypes were available. Three CRHBP SNPs rs6453267, rs7728378 and rs10474485 showed a nominally significant interaction with the continuous CTQ score to predict suicide attempt; rs7728378 remained significant after FDR correction. There was an additive effect with FKBP5: in the group exposed to high trauma, the prevalence of suicide attempt was 0.35–0.30 in carriers of either the FKBP5 rs3800373 major homozygote or the CRHBP rs7728378 major homozygote and 0.58 in carriers of both major homozygotes. Individuals without either major homozygote were resilient to the effects of childhood trauma (suicide attempt prevalence 0.24). Main effects of CRHBP rs6453267 and CRHR1 rs9900679, both unique to African ancestry, were detected. CRHBP variation may predispose, independently and additively, to suicidal behavior in individuals who have experienced childhood trauma.